The Effect of Progressive Muscle Relaxation on Fear of Childbirth in Primigravida Mothers - Diah Evawanna Anuhgera; Yohana Putri Apryanti; Lidia Lushinta (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Pregnancy and childbirth are extraordinary physiological experiences but can also be a source of psychological stress for women, especially for primigravidas who have no previous experience. Fear of childbirth often arises from uncertainty about pain management, concerns about the fetus's condition, and a lack of adequate information. This condition results in increased stress, sleep disturbances, and even mild depression, which can affect the mother's physical and mental readiness for childbirth. This study aims to analyze the effect of progressive muscle relaxation on fear of childbirth in primigravida mothers. The type of research used is an experimental study with a pretest-posttest without a control group. The sample consisted of third-trimester primigravida pregnant women who met the inclusion criteria, using a purposive sampling technique. The intervention in the form of progressive muscle relaxation exercises was given for 2 weeks at a frequency of three times per week and independent practice at home. The research instruments used were the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ), a demographic and obstetric history questionnaire, and a compliance sheet. Data analysis used dependent and independent t-tests. The results showed a significant decrease in fear of childbirth scores after progressive muscle relaxation with a p-value of 0.001. In conclusion, progressive muscle relaxation training is effective in improving the physical and psychological readiness of primigravida mothers for childbirth. This study recommends that health workers, particularly midwives, integrate progressive muscle relaxation training as a non-pharmacological intervention in prenatal classes.